Organizational commitment and the new workforce: a review of antecedents, outcomes and relevance - Ismail, Zakaria (Universiti Utara Malaysia, 2004)
Organizational commitment is an important organizational concept in the study of employee work behavior, especially withdrawal behavior. It was the focus of employee behavioral study for about four decades until in the late 1990s when people began to question the usefulness or the relevancy of the construct especially among the new workforce. This article reviews the concept of organizational commitment, and the development of multiple-dimensional constructs. This article also reviews its antecedents and outcomes. There is a long list of possible antecedents, but these can be categorized into organizational variables (e.g., organizational support, organizational dependability, leadership), job related variables (e.g., job characteristics, empowerment,role conjlict and ambiguity), and individual variables (e.g., age, gender,educational levels). The outcome variables which are consistently related to organizational commitment are turnover intention and absenteeism, and to a certain extent, work performance. The issue of the relevance of commitment was also reviewed, and this paper concludes that it is too early to write off organizational commitment, as recent empirical evidence indicated that organizational commitment is still a useful concept in the study of professionals,and the new workforce. This article suggests that future research in organizational commitment needs to focus especially on organizations undergoing downsizing, mergers and acquisitions, and among the new workforce such as Generation-X employees, knowledge workers, and telecommuters.